The Formation of a Unified Legislation in the Framework of the EAEU - D. V. Kozlov (Евразийская интеграция: экономика, право, политика, 2020)
The successful functioning of the EАEU is impossible without creating an array of legal documents that ensure its further integration development. The current state of Eurasian law leaves much to be desired. It develops chaotically, haphazardly and requires significant human and organizational costs. The article suggests using digital technologies in the legal sphere for the development of integration legislation of the EАEU. It is proposed to use graph theory for the selection and analysis of legal documents. The entire regulatory framework of the EАEU member States should be presented as big data. As a result, all the initial rough work will be done by machines, and the person will make the final conclusions. In the future, it is possible to create legislation of the EАEU on the branches of law.